Influence of Marketing and Advertising on Efficiency of the Pharmaceutical Distribution Services - MORDOVCHENKOV, Nikolay V.; MITROSHKINA, Larisa N.; TIKHOMIROV, Gennady A.; PANINA, Elena V. (Journal of Advanced Research in Law and Economics; Vol 8 No 2 (2017): Volume VII, Issue 2(24), Spring 2017, 2017)
This article is of the methodological type and dedicated to the search of optimization model of marketing integration into the process of effective functioning of pharmaceutical distribution services at the meso-level. The purpose of this publication is to develop recommended practices on interaction of the pharmaceuticals production and pharmaceutical marketing while transforming pharmaceutical distribution services at the meso-level and increasing their efficiency. The cause-and-effect relationship at the pharmaceutical market between the pharmaceuticals production and industrial marketing, between the pharmaceutical distribution services production and social marketing, is determined. The functional model of the production process of pharmaceuticals and the economic feasibility of their cost is presented. The functional dependence of the growth of the consumer’s demands for pharmaceuticals from the use of marketing and efficiency of pharmaceutical distribution services is shown. The effect of the intellectual capital on the infrastructure of the pharmaceutical distribution services of the region is defined. A complex, systematic approach to advertising is analyzed. The significance of the distributor in the process of the population sanitation is determined. Methods for determining of the value of the unsatisfied demand for pharmaceuticals are given and a tabular model of information resource of the unsatisfied demand for pharmaceuticals at the meso-level is presented.